Study on Optimization Technology to Strengthen Ni-Based Composite Coating Electroplate Containing Nanodiamond - Liu, Meihua (Materials (Basel), 2019)
Ni-based composite coating containing nanodiamonds was deposited on the substrate of Q235A low-carbon steel in a traditional Watts solution, without any additive. The nanodiamond grains prepared by detonation synthesis were measured by Transmission electron microscope (TEM) and X-ray diffraction (XRD). The electrochemical behavior of Ni(2+) ion in the composite bath including nanodiamonds was studied by linear sweep voltammetry experiments, and the morphology, elastic modulus, and hardness of Ni-based composite coating were characterized using Scanning Electron microscope (SEM) and the nano-indenter XP tester. Effects of the nanodiamond concentration in the bath, stirring speed, and the electroplate mode on the properties of Ni-based composite coating were investigated. The results show that the reduction of Ni(2+) ion in the electroplating process increased initially, and then decreased as the nanodiamond concentration in the bath increased from 4 g/L to 16 g/L, irrespective of whether direct current (DC), single-pulse, or double-pulse electroplating mode was used. The highest over-potential could be obtained when the nanodiamond concentration in the bath was 8 g/L. Moreover, the hardness and elastic modulus of the composite coating prepared by the DC electroplating mode were 4.68 and 194.30 GPa, respectively. By using the same plating parameters, the coating prepared by the double-pulse electroplating mode showed better properties, with hardness and elastic modulus values of 5.22 and 197.38 GPa, respectively.